(untitled) (Swiss Medical Weekly, 2021)
AIM OF THE STUDY For tumours of the oral tongue, the most recent 8th edition of the AJCC/UICC staging system has introduced depth of infiltration (DOI) as a novel parameter. With this study we wanted to investigate its impact regarding this risk stratification compared with the preceding 7th edition. METHODS Between 2008 and 2017, 161 patients of two tertiary referral centres in Switzerland (Kantonsspital St. Gallen and University Hospital Zurich) with T1 N0 or T2 N0 tongue cancers were enrolled in this study. The primary tumours were restaged according to the 8th edition of the TNM classification. Kaplan-Meier curves for overall and disease-specific survival were calculated. RESULTS According to the 7th edition, of the 161 patients, 102 were staged after surgery as pT1 (stage I) and 59 as pT2 (stage II). According to the 8th edition, 36 patients (22.4%) were re-staged to a higher stage. Of these 36 patients, 8 (22.2%) experienced a recurrence, and 9 (25%) died. In the remaining, not re-staged group, 20 patients (16.0%) experienced a recurrence (p = 0.55) and 14 (11.2%) died (p = 0.025*). The 7th edition showed a statistically significant difference between pT1 and pT2 tumours for overall survival (p = 0.025), but not for disease-specific survival (p = 0.091), whereas the 8th edition was able to well discriminate between pT1, pT2 and pT3 for both overall (pT1 vs pT2, p = 0.016*; pT2 vs pT3, p = 0.031*) and disease-specific survival (pT1 vs pT2, p = 0.037*; pT2 vs pT3, p = 0.023*). CONCLUSION The recent TNM 8th edition provides a more accurate prediction of overall and disease-specific survival for this subgroup of patients. Hence, a more aggressive treatment should be considered for patients re-staged to pT3 due to depth of infiltration.